[68Ga]-Pentixafor PET/CT for CXCR4-Mediated Imaging of Vestibular Schwannomas - Breun, Maria; Monoranu, Camelia M.; Kessler, Almuth F.; Matthies, Cordula; Löhr, Mario; Hagemann, Carsten; Schirbel, Andreas; Rowe, Steven P.; Pomper, Martin G.; Buck, Andreas K.; Wester, Hans-Jürgen; Ernestus, Ralf-Ingo; et al. (Frontiers in Oncology, 2019)
.We have recently demonstrated CXCR4 overexpression in vestibular schwannomas (VS). This study investigated the feasibility of CXCR4-directed positron emission tomography/computed tomography (PET/CT) imaging of VS using the radiolabeled chemokine ligand [68Ga]Pentixafor. METHODS: 4 patients with 6 primarily diagnosed or pre-treated/observed VS were enrolled. All subjects underwent [68Ga]Pentixafor PET/CT prior to surgical resection. Images were analyzed visually and semi-quantitatively for CXCR4 expression including calculation of tumor-to-background ratios (TBR). Immunohistochemistry served as standard of reference in three patients. RESULTS: [68Ga]Pentixafor PET/CT was visually positive in all cases. SUVmean and SUVmax were 3.0±0.3 and 3.8±0.4 and TBRmean and TBRmax were 4.0±1.4 and 5.0±1.7, respectively. Histological analysis confirmed CXCR4 expression in tumors. CONCLUSION: Non-invasive imaging of CXCR4 expression using [68Ga]Pentixafor PET/CT of VS is feasible and could prove useful for in vivo assessment of CXCR4 expression.